2013
DOI: 10.1001/jamaoto.2013.3863
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy in Lieu of Neck Dissection for Staging Oral Cancer

Abstract: The majority of patients with positive results on SNB had additional positive nodes on neck dissection. A low rate of isolated neck recurrence was found in patients with negative results on SNB. Individuals with negative results on SNB exhibited better overall and disease-specific survival than those with positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 11 publications
1
23
0
1
Order By: Relevance
“…For SND/ND demonstrating greater than one positive lymph node or with extracapsular spread, perineural or perivascular spread, adjuvant chemoradiotherapy was recommended for definitive, further management. These recommendations were based upon previous clinical experience and studies published on SNB . All patients who underwent further adjuvant therapy after ND received chemoradiotherapy with cisplatin‐based regimens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For SND/ND demonstrating greater than one positive lymph node or with extracapsular spread, perineural or perivascular spread, adjuvant chemoradiotherapy was recommended for definitive, further management. These recommendations were based upon previous clinical experience and studies published on SNB . All patients who underwent further adjuvant therapy after ND received chemoradiotherapy with cisplatin‐based regimens.…”
Section: Methodsmentioning
confidence: 99%
“…Controversy exists regarding the consequences of SND in patients with a clinically negative neck with no found nodal disease. Studies indicate that early stage OSCC presents with cervical node metastasis in about 20% to 30% of cases . As such, clinical observation in the cN0 may be a viable option to avoid the morbidity of SND.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The techniques and methodology for SLN identification in head and neck cancers have been widely debated and are still under investigation [ Tables 1 and 2]. 5,14,15,22,24,[27][28][29][30][31][34][35][36][37][38][39][40][41][42][43][44][45][46] Shoaib et al suggested a protocol involving preoperative lymphoscintigraphy, intraoperative blue dye and gamma probe localisation [ Figure 2]. 30 This technique is based on observing the route of lymphatic flow via imaging after the injection of a radioactive contrast agent near the primary tumour.…”
mentioning
confidence: 99%
“…1,10,11 Even with the application of sentinel node biopsy, 6% to 9% of the occult nodal metastases still remain undetected. 12,13 The presence of neck nodal metastases is a crucial prognostic determinant for the patient's Upon completion of this activity you will be able to: • describe which tumor characteristics of an oral squamous cell carcinoma (OSCC) are associated with regional (nodal) metastasis. • list the "unfavorable" growth parameters of an OSCC associated with regional metastasis.…”
mentioning
confidence: 99%